What Causes Gender Differences in the Participation and Intensity of Lifelong Learning? - Peter Huber; Ulrike Huemer (Austrian Institute of Economic Research (WIFO), 2009)
We use recent advances in the statistical analysis of Oaxaca-Blinder decompositions for non-linear models to analyse the contribution of individual variables to total gender differences in participation and duration of training. Results suggest that effects stemming from the intra-household division of labour contribute significantly to gender differences, but that segregation of the labour market as well as differences in the access to training by tenure, age, occupation, profession and sectors are more important.
Keywords: 330; gender differences; training; Lebenslanges Lernen; Geschlecht; Hausarbeit; Weibliche Arbeitskräfte; Österreich